DAMPAK NORMALISASI HUBUNGAN DIPLOMATIK ISRAEL DAN NEGARA-NEGARA ARAB TERHADAP KEBIJAKAN LUAR NEGERI INDONESIA DI TIMUR TENGAH - Hakiem, Fadhlan Nur; Putri, Lolita Deby Mahendra; Gustianti, Nurbani Adine (Universitas Jenderal Ahmad Yani, 2023)
The research aims to understand the impact of the normalization of diplomatic relations between Israel and Arab countries on Indonesia's foreign policy in the Middle East. The signing of the Abraham Accords in 2020 is a new chapter in relations between Israel and Arab countries. Four Arab countries - the United Arab Emirates, Bahrain, Sudan, and Morocco - decided to normalize diplomatic relations with Israel. This has an impact on political dynamics in the Middle East region. Indonesia, the country with the largest Muslim population in the world and a country that consistently fights for Palestinian independence, has the potential to be affected by the normalization of diplomatic relations. This research used qualitative research methods which were descriptive analysis. The data collection technique used was literature study. The data analysis technique used in this research was content analysis. The research results show that Indonesia's foreign policy is not affected by the normalization of diplomatic relations between Arab countries and Israel. Indonesia is consistent in fighting for peace and the fate of the Palestinian people in accordance with international parameters, UN resolutions and the Arab Peace Initiative.